Kesehatan Mental Generasi Z dalam Era Digital: Studi Psikologis tentang Kecemasan Sosial dan Ketergantungan Media Sosial - Chaniago, Salsabila Najma (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2025)
The development of digital technology has had a significant impact on the behavior and mental health of Generation Z, particularly in the context of intensive social media use. Generation Z is known as a generation born and raised in the digital era, so their social interactions are heavily influenced by the virtual world. The phenomenon of increasing social anxiety and dependence on social media has become an increasingly complex and relevant psychological issue for research. This study aims to analyze the relationship between social anxiety and social media dependence in Generation Z from a modern psychological perspective. This study uses a qualitative approach based on library research by examining theories of developmental psychology, social psychology, and empirical data from various relevant scientific journal articles. The results show that excessive social media use is positively correlated with increased symptoms of social anxiety such as fear of judgment from others, avoidance of social situations, and discomfort in face-to-face interactions. Dependence on social validation in the form of "likes" and comments also reinforces the cycle of anxiety, forming passive-aggressive interaction patterns and social comparisons that negatively impact self-esteem. Furthermore, social media algorithms that trigger repeated content consumption reinforce emotional dependence, causing users to feel trapped by unrealistic social expectations. In conclusion, social anxiety and social media dependence in Generation Z reinforce each other and form a cycle that has a serious impact on mental health, so a multidisciplinary approach is needed to address this problem comprehensively.